Design of a flexible modified rectangular dual-band antenna for ISM bands with SAR analysis - Mohan Chinnasamy; Uma Mariappan; Charulatha Gopinathan; Ashokkumar Mani; Anita Daniel; Sree Devi Baskaran (Institute of Advanced Engineering and Science, 2026)
Regarding dual industrial, scientific, and medical (ISM) band utilization, a planar, high-gain, dual-band modified antenna has been implemented application. This modified antenna features a rectangular patch with combined slots. This antenna has a profile of approximately 0.25 λ0×0.18 λ0. The combination of slots and modified rectangular patch allows for multiple-band performance. The designed antenna operates in two bands: 5.81 GHz and 2.42 GHz wireless body area network (WBAN). The antenna offered maximum radiation efficiencies of 76.4% and 82.8% in the two operating bands, with peak gains of 3.43 dB and 3.81 dB. The suggested antenna has reflection coefficients of -28.3 dB at 2.43 GHz and -23.9 dB at 5.81 GHz, respectively. The antenna's safety features were additionally evaluated employing a threelayer human body phantom initiated of fat, muscle, and skin tissues. The specific absorption rate (SAR) of the proposed antenna was evaluated using a three-layer human tissue model representing skin, fat, and muscle. The calculated SAR values were analysed according to the IEEE C95.1-1999 and IEEE C95.1-2005 safety guidelines, and the results confirm that the antenna operates within the permissible exposure limits. The measured results closely match simulations, demonstrating its reliability. Owing to its compact size, improved efficiency, strong impedance performance, and validated safety compliance, the proposed antenna is much impressed for effective ISM band communications.